The Effect of Governance, Risk, Compliance (GRC) And Intellectual Capital On Company Value Through Financial Performance - Afriyani, Neni; Kamaliah, K.; Indrawati, Novita (Manunggal Halim Jaya, 2025)
This study examines and analyzes the effect of Governance, Risk, and Compliance (GRC) and Intellectual Capital on firm value, with financial performance mediating variables in banking companies. The population in this study includes all banking companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. The sample was selected using a purposive sampling method. The data used are secondary data sourced from annual reports and financial statements. The data analysis technique employed in this study is Partial Least Squares (PLS) using SmartPLS 4 software. The results show that GRC has no significant effect on financial performance or firm value. Intellectual Capital does not directly affect firm value, but significantly and positively influences financial performance. Furthermore, financial performance itself has no significant effect on firm value. The mediating effect analysis indicates that financial performance does not mediate the relationship between GRC and firm value, nor between Intellectual Capital and firm value.